To renovate or build with wood? Results from Finnish citizen survey data - Ruokamo, Enni; Franzini, Florencia; Lähtinen, Katja; Toppinen, Anne (Taylor & Francis, 2024)
Finland shows strong support for reducing its climate footprint originating from the built environment as part of the national carbon neutrality goal by 2035. Two prime examples are increasing wood use in construction and favoring building renovation to alleviate emissions from the use of virgin construction materials. However, the open question remains whether citizens also support these decarbonization pathways. By using national-level data from a randomly sampled citizen survey in Finland (n = 1448), we model citizen preferences to these two decarbonization pathways. The results suggest that a preference to renovate rather than to build anew is shown by respondents of the female gender; over 55 years of age; with a lower household equivalent income; and possessing housing property investment. Wood material is positively favored by respondents with higher age; a lower household equivalent income; living in smaller population centers in the countryside; and owning forestland. Interestingly, the effect of climate agency was negative in both models. This can be interpreted in the wood material case as reflecting conflicting views of negative environmental effects from forest harvesting to produce renewable building materials. In the renovation model case, we argue that the climatic impact of renovations remain weakly understood by citizens in Finland, given that the media and national regulations emphasize operational emissions. These results benefit both policy makers and municipal-level decision making in understanding of acceptability of wood material use and building retrofits among the general public.
Keywords: housing characteristics; climate agency; renovation; survey data